Corrigendum to "Development of congklak-based ethnomathematics media for teaching fractional numbers to grade V students” - Alfinda Dwi Ninggar; Arina Restian; Murtyas Galuh Danawati (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
In the original published version of this article, the authors incorrectly added email dwnalfindaalfindadwi3003@gmail.com as the email address for Alfinda Dwi Ninggar. The email address has now been corrected. The authors apologize for the error. The PDF versions of the article have been updated to correct the errors.________________________Original article & DOI: http://dx.doi.org/10.33578/jpfkip-v13i4.p171-183